Pengaruh Media Video terhadap Pengetahuan dan Sikap Tentang Pemeriksaan Payudara Sendiri (Sadari) pada Siswi SMA Negeri 1 Labuhan Deli - zalfa azalia; Reni Agustina Harahap; Sahrul Sahrul; Zuhrina Aidha; Dewi Agustina (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Breast cancer is one of the leading causes of death in women in Indonesia, with a tendency for patients to become younger. Early detection through Breast Self-Examination (BSE) plays a crucial role in reducing the risk of delayed diagnosis, but young women's knowledge and attitudes regarding BSE remain low. Video media is considered an effective health promotion strategy for increasing knowledge and shaping attitudes. This study aims to analyze the effect of video media on knowledge and attitudes about BSE among female students at SMA Negeri 1 Labuhan Deli. The method used in this study was quantitative with a pre-experimental research design with a one-group pretest–posttest conducted at SMA Negeri 1 Labuhan Deli. The sample consisted of 45 female students in grades 10 and 11 selected through purposive sampling. Data were collected using a questionnaire. Before the intervention, the majority of respondents had sufficient knowledge (53.3%) and attitudes (80.0%). After the intervention, all respondents (100%) had good knowledge and 97.8% had good attitudes. The Wilcoxon test results showed a p-value of 0.000 for both variables, indicating a significant effect of video media on improving female students' knowledge and attitudes about BSE. Video media has proven effective as a health promotion medium to increase awareness of young women in early breast cancer detection.